84 Evaluation of hair coat shedding ability as an adaptive trait in Angus cattle in the southern U.S. (28th November 2020) - Burnett, Randy H; Duvic, Morgan A; Kutz, Bryan R; Brown, Avert H; Powell, Jermey G; Smith, Trent; Riley, David G; Cauble, R N
Abstract: The objective of this study was to evaluate winter hair coat shedding ability and the association to cow production performance. This work was a collaborative effort from the S-1064 multi-state research project. Data were collected on spring and fall-calving purebred and commercial Angus females with calves (n = 1192) from March until July from 2008 to 2018 in Mississippi, Arkansas and Texas. Dams were observed once monthly by two trained technicians for winter hair coat shedding and give a visual hair shedding score of 1 to 5 with 1 indicating 100% shed, 2 = 75% shed, 3 = 50% shed, 4 = 25% shed, and 5 indicating 0% shedding of the winter hair coat. Month of first shedding (MFS) was determined once a female reached an average hair shedding score of ≤ 3.5 for any given month. Calf birth and weaning weights were considered as performance of the dam. For cow performance, the response variables included AdjBW and d205wt of the calf. Data were analyzed using the MIXED procedure of SAS with significance declared at P ≤ 0.05. The model included MFS as a fixed effect with calf sex as a covariate and calf sire as a random effect. Females that obtained a shedding score of ≤ 3.5 by May had heavier calves at birth (P ≤ 0.01) when compared with those that shed in June and July, with July weights being the lightest. Females that scored ≤ 3.5 by May has significantly heavier d205wt (P ≤ 0.01) when compared to those that shed by June and July. When comparing locations, females in Arkansas shed later (P ≤ 0.01) when compared with both Mississippi and Texas, which were similar. Shedding ability could be an important economic trait to be considered in cow-calf operations.